Integrasi Pemanfaatan Media Sosial dalam Pembelajaran Pendidikan Agama Islam Berbasis Moderasi Beragama dan Pluralisme untuk Penguatan Karakter Peserta Didik: Studi Literatur Kebijakan Pendidikan - Idham Cholid; Suwoko Suwoko; Siti Hardianti (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2026)
The development of digital technology, particularly social media, has brought significant changes to the teaching and learning practices of Islamic Religious Education (PAI). On the other hand, the rising phenomena of intolerance, the spread of extremist religious ideologies, and moral degradation among the younger generation demand innovations in PAI learning that can strengthen students' character. This study aims to analyze the integration of social media utilization in PAI learning based on religious moderation and pluralism as an effort to strengthen students' character from an educational policy perspective. This study employed a qualitative approach with a Systematic Literature Review (SLR) design adhering to the PRISMA guidelines. Data sources were obtained from reputable national and international journal articles, academic books, and educational policy documents published between 2015 and 2026 through the Google Scholar, Scopus, ScienceDirect, and Garuda databases. The data were analyzed using content analysis and thematic analysis techniques. The results indicate that the utilization of social media in PAI learning contributes to increasing students' motivation, participation, and independent learning. Furthermore, social media can serve as an effective medium to internalize the character values of religiosity, religious moderation, and pluralism through the presentation of dialogic, reflective, and inclusive religious content. This study also finds that the integration of social media in PAI learning aligns with the direction of national educational policies that emphasize the strengthening of character education, digital transformation in education, and the development of moderate religious attitudes. This study offers a conceptual contribution in the form of an integrative model for utilizing social media based on religious moderation and pluralism in PAI learning as a strategy to strengthen students' character in the digital era.